Female obesity increases the risk of preterm birth of single frozen-thawed euploid embryos: a retrospective cohort study - Xitong Liu; Juanzi Shi (Taylor & Francis Group, 2024)
AbstractIntroduction Obesity has been associated with an increased risk of reproductive failure, especially preterm birth. As preimplantation genetic testing for aneuploidies (PGT-A) is increasingly used worldwide, however, it is still unclear whether body mass index (BMI) has an effect on the preterm birth rate in patients undergoing in vitro fertilization (IVF) with PGT-A when transferring a single euploid blastocyst.Materials and methods This retrospective, single-center cohort study included 851 women who underwent the first cycle of frozen-thawed single euploid blastocyst transfer with PGT-A between 2015 and 2020. The primary outcome was the preterm birth rate. Secondary outcomes were clinical pregnancy, miscarriage, ectopic pregnancy, pregnancy complications, and live birth.Results Patients were grouped by World Health Organization (WHO) BMI class: underweight (<18.5, n = 81), normal weight (18.5-24.9, n = 637), overweight (25-30, n = 108), and obese (≥30, n = 25). There was no difference in the clinical pregnancy, miscarriage, ectopic pregnancy, pregnancy complication, and live birth by BMI category. In multivariate logistic regression analysis, preterm birth rates were significantly higher in women with overweight (adjusted odds ratio [aOR] 3.18; 95% confidence interval [CI], 1.29-7.80, p = .012) and obese (aOR 1.49; 95% CI, 1.03-12.78, p = .027) compared with the normal weight reference group.Conclusion Women with obesity experience a higher rate of preterm birth after euploid embryo transfer than women with a normal weight, suggesting that the negative impact of obesity on IVF and clinical outcomes may be related to other mechanisms than aneuploidy.